Dynamic evaluation of circulating tumour cells in patients with advanced gastric and oesogastric junction adenocarcinoma: Prognostic value and early assessment of therapeutic effects. (July 2017) - Pernot, Simon; Badoual, Cecile; Terme, Magali; Castan, Florence; Cazes, Aurelie; Bouche, Olivier; Bennouna, Jaafar; Francois, Eric; Ghiringhelli, Francois; De La Fouchardiere, Christelle; Samalin, Emmanuelle; Bachet, Jean Baptiste; et al.
Abstract: Background: The identification of dynamic biomarkers in advanced gastric and oesogastric junction adenocarcinoma (GOA) could help to tailor strategies for each patient. Enumeration of circulating tumour cells (CTCs) is approved by the US Food and Drug Administration in breast, colon and prostate cancer but is not in advanced GOA. Our study aims to establish the optimal threshold and the clinical significance of CTC count in advanced GOA before and during treatment. Methods: One hundred six patients with untreated advanced GOA were included in the ancillary study of the PRODIGE 17-ACCORD 20 trial. CTCs were detected in the peripheral blood using the CellSearch system on day 0 (D0) and day 28 (D28). The prognostic value of CTCs at D0 and D28 was analysed by testing several thresholds. Results: At baseline, median CTC count was 1 (range, 0–415). While CTCs ≥1, 2 or 3 at D0 were all significantly associated with worse overall survival (OS) and progression-free survival (PFS), CTCs ≥2 were the optimal threshold, on D0 or D28. CTCs ≥2 at D28 were also predictive of disease control. Taking into account both D0 and D28 CTC count defined 3 groups (low/low, high/low and low-high/high) with significantly different PFS (p = 0.0002) and OS (p = 0.003). Conclusion: Quantification of CTCs at baseline and during treatment may be a useful prognostic tool in advanced GOA, as it is associated with worse PFS and OS. A threshold ≥2 CTCs seems to have the best discriminant value. Change in CTC count between baseline and D28 could help to tailor treatment to each individual patient. Highlights: Circulating tumour cells (CTCs) count at baseline and day 28 is a strong prognostic factor in advanced gastric cancer. CTC count at day 28 is also predictive of disease control. Therefore, evolution of CTC count between baseline and D28 could help to early adjust treatment.